Three Quenched, Faint Dwarf Galaxies in the Direction of NGC 300: New Probes of Reionization and Internal Feedback - David J. Sand; Burçin Mutlu-Pakdil; Michael G. Jones; Ananthan Karunakaran; Jennifer E. Andrews; Paul Bennet; Denija Crnojević; Giuseppe Donatiello; Alex Drlica-Wagner; Catherine Fielder; David Martínez-Delgado; Clara E. Martínez-Vázquez; et al. (The Astrophysical Journal Letters)
We report the discovery of three faint and ultrafaint dwarf galaxies—Sculptor A, Sculptor B, and Sculptor C—in the direction of NGC 300 ( D = 2.0 Mpc), a Large Magellanic Cloud–mass galaxy. Deep ground-based imaging with Gemini/GMOS resolves all three dwarf galaxies into stars, each displaying a red giant branch indicative of an old, metal-poor stellar population. No young stars or H i gas are apparent, and the lack of a GALEX UV detection suggests that all three systems are quenched. Sculptor C ( D = 2.04 ${}_{-0.13}^{+0.10}$ Mpc; M _V =  −9.1 ± 0.1 mag or L _V = (3.7 ${}_{-0.3}^{+0.4}$ ) × 10 ^5 L _⊙ ) is consistent with being a satellite of NGC 300. Sculptor A ( D = 1.35 ${}_{-0.08}^{+0.22}$ Mpc; M _V = −6.9 ± 0.3 mag or L _V = (5 ${}_{-1}^{+1}$ ) × 10 ^4 L _⊙ ) is likely in the foreground of NGC 300 and at the extreme edge of the Local Group, analogous to the recently discovered ultrafaint Tucana B in terms of its physical properties and environment. Sculptor B ( D = 2.48 ${}_{-0.24}^{+0.21}$ Mpc; M _V = −8.1 ± 0.3 mag or L _V = (1.5 ${}_{-0.4}^{+0.5}$ ) × 10 ^5 L _⊙ ) is likely in the background, but future distance measurements are necessary to solidify this statement. It is also of interest due to its quiescent state and low stellar mass. Both Sculptor A and B are ≳2–4 r _vir from NGC 300 itself. The discovery of three dwarf galaxies in isolated or low-density environments offers an opportunity to study the varying effects of ram-pressure stripping, reionization, and internal feedback in influencing the star formation history of the faintest stellar systems.